The impact of maternal asthma during pregnancy on fetal growth and development: a review. (1st December 2020) - Meakin, Ashley S.; Saif, Zarqa; Seedat, Nabila; Clifton, Vicki L.
ABSTRACT: Introduction: Asthma is a highly prevalent co-morbidity during pregnancy that can worsen as gestation progresses and is associated with several adverse perinatal outcomes. These adverse outcomes often result from uncontrolled asthma during pregnancy and acute asthma exacerbations that are associated with alterations in placental function and fetal growth. Areas covered: This paper will discuss how maternal asthma in pregnancy affects fetal growth and development which may alter future offspring health. Changes in placental function occur in a sex-specific manner in pregnancies complicated by asthma and result in differences in fetal growth and development which may influence child health. The follow up of children from mothers with asthma suggests they are at greater risk of developing asthma, have alterations in microvascular structure that may contribute to a future risk of cardiovascular disease and epigenetic modifications in immune cell function. The current evidence suggests that appropriately managed asthma during pregnancy results in normal fetal growth and development. Expert opinion: Clinical management of asthma during pregnancy needs significant improvement to prevent adverse outcomes for the fetus. The key to improving maternal and fetal outcomes is through education of health professionals and parents about controlling asthma during pregnancy.